First record of Cravenia panduriformis (Hibisceae, Malvaceae) in the Flora of Egypt - Badry, Mohamed O.; Osman, Ahmed K.; Ayed, Fatma A.; Zaki, Hoida; Fayaz, Ahmed; Sheded, Mohamed G. (Phytotaxa, 2026)
As part of the floristic surveys documenting ongoing updates to the Egyptian flora through systematic revisions, Cravenia panduriformis is recorded as a new genus and species record from the Aswan Reservoir area, a novel contribution to the flora of the Nile region. The present study provides a comprehensive description of this taxon’s morphological, anatomical, palynological, and seed coat features. The study reports the chromosome number (2n = 24) for the Egyptian population of Cravenia panduriformis, adding new cytogenetic data to complement previous records from other geographic regions. Furthermore, it includes observations regarding its habitat and presents images for easy identification.